Simplifier des expressions avec la fonction logarithme Exercice

Simplifier l'expression suivante :

\(\displaystyle{A = \ln\left(9\right) - \ln\left(3\right) +2\ln\left(\sqrt 3\right)}\)

Simplifier l'expression suivante :

\(\displaystyle{A = \ln \left(\dfrac{1}{2}\right) + \ln 4}\)

Simplifier l'expression suivante :

\(\displaystyle{A = \ln 7 +\ln 49}\)

Simplifier l'expression suivante :

\(\displaystyle{A = \ln \left(\dfrac{2}{5}\right) +\ln 25}\)

Simplifier l'expression suivante :

\(\displaystyle{A = 2\ln x - \ln 3x}\)

Simplifier l'expression suivante :

\(\displaystyle{A = \ln\left(x^2+2x+1\right) - \ln\left(x+1\right)}\)

Simplifier l'expression suivante :

\(\displaystyle{A = \ln\left(\sqrt{2x+3}\right) +\ln \left(2x+3\right)^3}\)

énoncé suivant